Caregivers’ care experiences of children with developmental dislocation of the hip in Tibet, China: a convergent mixed-methods study - Lei, Yang; Yan, Jiang; Wenjuan, Shao; Weili, Shen; Qianyi, Xiao; Lingyan, Fan (Frontiers in Pediatrics, 2025)
AimTo understand, comprehensively, care experiences of caregivers for children with developmental dislocation of the hip in Tibet, China.BackgroundPostoperative rehabilitation for children with developmental dislocation of the hip (DDH) may last for several months to years. Even after discharge, recovery is often partial. It is important to note that despite optimal surgical treatment, lifelong residual issues may persist, such as limping, chronic pain, or early-onset osteoarthritis. Home care is critical in postoperative recovery. Family as the basic unit of home-based care for patients, many measures are inevitably carried out in the family environment and rely on family caregivers to provide. This requires caregivers to pay long-term and high attention, posing significant challenges to caregiving capacity.DesignA convergent mixed-methods.MethodsCaregivers (n = 76) completed the Chinese version of the Family Caregiver Care Ability Scale, the Zarit Caregiver Burden Scale and 12 participated in semi-structured interviews from September, 2023 to February 2024. Descriptive statistics and Pearson correlation analysis were used for quantitative analysis, thematic analysis for qualitative analysis. Both quantitative and qualitative data were merged and integrated for mixed-methods analysis.ResultsLow caregiver capacity and moderate caregiver burden scores were reported. Four themes emerged from care experiences: different emotions at different stages (initial worry, backend trust), caregiving process overwhelmed (role conflict, lack of caregiving capacity), insufficient information (disease-specific information, actual care information), and social support.ConclusionThis study is the first to use this mixed-methods design to analyze the current state of care and burden among family caregivers of children with developmental dislocation of the hip in Chinese highland region-Tibet. The combined results showed that qualitative results converged with quantitative results in terms of emotional changes, role burden, lack of disease-specific information, and social support; qualitative results complemented quantitative results in terms of caregiving capacity deficits and lack of actual care information to explain the quantitative results. The quantitative findings also emphasized the link between social support in terms of caregiving capacity and caregiving burden. These results guide future research to promote rehabilitation and improve quality of life for affected children and families.